Role of media in motivating career-oriented females in challenging the norms of patriarchy. (22nd January 2020) - Gupta, Priya; Sharma, Mili
The present study begins with a pertinent question. Do women have a choice on whether they want to embrace motherhood, or are they socialised so effectively into the role almost from their own birth that they do not recognise it as one? If marriage is near universal in India, so is motherhood - there is little scope for choice here. Now the major problem arises that "Is it necessary for career-oriented women to get married and sacrifice their career for the sake of family and motherhood?" or why cannot a career-oriented woman pursue her career and enjoy motherhood without involving herself in the intricacies of marriage? The study, with the help of focus group discussions, spread across four stratums aims to provide answers to these questions. It tries to make a case for surrogacy and in-vitro fertilisation (IVF). It introduces the concept of 'single mothers by choice' or 'choice moms' and tries to understand the mindset of Indian women by analysing its advantages, disadvantages and consequences.